(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This scientific article deeply analyzes the mechanisms of artistic interpretation of the fate of the creator, in particular the artist, in modern Uzbek novels from a literary-theoretical and poetic perspective. The focus of the research is on the problem of the creation of the fate of the creator in the novel as a purely artistic model and its reshaping through artistic-biographical reconstruction. The article analyzes the manifestation of the image of the artist in the novel “Moon and Chaqa” as a purely artistic construction based on the author’s aesthetic consciousness, devoid of real biographical logic, and the poetic analysis of the artistic-biographical model resulting from the artistic processing of the life of a historical figure in the novel “The Last Will of Rozi Choriev”. These two interpretations of the fate of the creator are considered at the intersection of Eastern and Western aesthetic thinking, and it is scientifically substantiated that the image of the artist in the novel is not a factual image, but an artistic expression of an aesthetic concept. The results of the study show that in the novel, the fate of the creator is determined not by biographical accuracy, but by the level of aesthetic generalization, and this situation means that the image of the creator in modern Uzbek novelism has risen to a new poetic level.